Retracted: Propranolol suppresses HUVEC viability, migration, VEGF expression, and promotes apoptosis by downregulation of miR‐4295. Issue 4 (28th October 2018) - Zhao, Feng; Yang, Xiaoliang; Xu, Guangqi; Bi, Jianhai; Lv, Renrong; Huo, Ran
Abstract: Infantile hemangioma (IH) is a common benign tumor. Human umbilical vein endothelial cells (HUVECs) have the potential of stem cells, which has been widely used in vascular endothelial cell experiments. Oral propranolol was first reported to treat hemangioma in 2008. However, the role of propranolol in IH remains unclear. Therefore, in this study, we investigated the effects of propranolol on HUVECs in vitro, to explore the underlying mechanism of propranolol in IH. HUVECs were treated with 0.15, 1.5, and 15 μM of propranolol, and transfected with microRNA‐4295 (miR‐4295) mimic. Cell viability, migration, and apoptosis were examined using Cell Counting Kit‐8, transwell assay, and flow cytometry analysis, respectively. In addition, the expressions and concentrations of miR‐4295, vascular endothelial growth factor (VEGF), VEGF‐A, FLT1, FLT2, and FOXF1 were assessed using real‐time polymerase chain reaction, Western blot assay, and enzyme‐linked immunosorbent assay. We found that 15 μM of propranolol decreased HUVEC viability the most. Then, cell migration and the concentrations of VEGF and VEGF‐A were reduced, and apoptosis was increased when treated with propranolol. Meanwhile, the expressions of VEGF, VEGF‐A, FLT1, FLT2, and FOXF1 were downregulated by propranolol exposure. Further study showed that miR‐4295 expression was upregulated in IH tissues, and propranolol treatment downregulated miR‐4295 expression in HUVECs. MiR‐4295 overexpression alleviated the reductions of viability, migration, and factors expression, as well as the increase of apoptosis. Propranolol suppressed HUVEC viability, migration, the expression of VEGF, VEGF‐A, FLT1/2,  FOXF1, and promoted apoptosis via downregulation of miR‐4295. This study lays a foundation for further study of the effect of propranolol on IH. Abstract : Propranolol suppressed human umbilical vein endothelial cells viability, migration, the expression of vascular endothelial growth factor, VEGF‐A, FLT1/2, FOXF1, and promoted apoptosis via downregulation of miR‐4295. This study lays a foundation for further study of the effect of propranolol on infantile hemangioma.